The Spatio Temporal Dynamic of Diffuse Attenuation Coefficient in the Tropical Berau Estuary, East Kalimantan Indonesia - Ambarwulan, Wiwin; Widiatmaka, Widiatmaka (Indonesian Journal of Geospatial, 2014)
Abstract. The availability of light in the water column determines the euphotic zone and constrains the type and the vertical distribution of benthic species. Diffuse attenuation coefficient (Kd) is an important apparent optical property (AOP) that provide information about the attenuation of the spectral down welling solar irradiance with depth in the water. Ocean color Satellite provide global coverage of optical water quality parameters at spatial and temporal resolution. Several empirical and semi-analytical models are commonly used to derive Kd at wavelength 490 nm Kd(490) from ocean colour satellite sensors. This study present about the diffuse attenuation coefficient, Kd(490) using semi-analytical approach. The dynamic Kd(490) in the Berau Estuary water was studied and compared with those derived from ocean color satellite sensor, Medium Resolution Imaging Spectrometer (MERIS). The study indicated that Kd(490) of in situ measurement had the best correlation with the Kd(490) of MERIS data of remote sensing reflectance (Rrs) derived with FUB (Free University Berlin) algorithm (R2=0,84). The dynamic of Kd(490) from MERIS data on different date indicated that the Kd(490) have a similar pattern and decreased when going to offshore.Â Keywords: MERIS, Secchi disc depth, tropical coastal water, Kd(490), a semi-analytical approach